Prospective Study About the Relationship Between CEUS of Carotid Intraplaque Neovascularization and Ischemic Stroke in TIA Patients - Li, Zhenzhou; Xu, Xianfeng; Ren, Lijie; Shao, Yufeng; Luo, Shuyu; Chen, Shenghua; Guan, Xiaoyun (Frontiers in Pharmacology, 2019)
Objective To evaluate the relationship between the contrast-enhanced ultrasonography(CEUS) of carotid intraplaque neovascularization and the ischemic stroke in TIA patient. Methods A total of 112 TIA patients were selected for the study. Routine carotid ultrasonic examination were done for all the patients. CEUS were done for consecutive patients with plaque thicker than 2.5mm in carotid bifurcation and follow-up for at least 24 months. The number of patients with incurrence of ischemic stroke or recurrence of TIA were gotten during the follow-up period. To detect the risk factors for incurrence of ischemic stroke or recurrence of TIA in 24 months, multivariate logistic regression analysis were performed for all the risk factors in all the selected patients. Results Ninety-one patients underwent the CEUS and were followed up at least 24 months. There were statistical differences between recurrent and non-recurrent groups about hypertension, diabetes, hyperlipemia, smoking history, family history of stroke, medication compliance, two-dimensional ultrasound and CEUS(P＜0.05). The higher CEUS intensity in the carotid plaque was, the higher possibility of ischemic stroke or recurrent TIA was. Multivariate logistic regression analysis showed that the CEUS characteristics of carotid plaque such as linear enhancement or diffuse enhancement were independent risk factors for ischemic stroke or recurrent TIA in TIA patients (P＜0.05). Conclusion For carotid plaques, CEUS could evaluate the infusion mode of them, which could reflect the neovascularization in plaques. CEUS could predict the incurrence of ischemic stroke or recurrence of TIA in TIA patients, which was useful information for clinical decision.